Limitations on the Types of Position of Migrant Workers Who Get Placement Fee Waiver Review from the Principle of Protection of Indonesian Migrant Workers - Nugraheni, Yonika Dani; Muttaqin, Labib (Jurnal Penelitian Ilmu-Ilmu Sosial, 2022)
Placement fees cannot be charged to Indonesian migrant workers. Therefore, BP2MI established BP2MI Regulation No. 09/2020 regarding the waiver of the placement fee for Indonesian migrant workers. One of the contents of the regulation only stipulates 10 types of positions for Indonesian migrant workers whose placement fees are waived. By using normative legal research that is descriptive in nature, the results obtained are that the BP2MI policy which only stipulates 10 types of positions for Indonesian migrant workers whose placement fees are freed is not in accordance with the concept of the welfare state adopted by the Indonesian state. Besides, when related to several principles of protection for Indonesian migrant workers, the criteria for the position of Indonesian migrant workers who should also receive exemption from placement fees include being vulnerable to discrimination, exploitation, violence, human trafficking practices, as well as threats of opinion and restrictions on access to movement.